Analyzing the Adoption of SIAKAD Service at Subang University Using UTAUT-3 - Untung Subagyo; Dedy Ardiansyah; Annisa Budi Utami; Bagus Ali Akbar (UPT Publikasi Ilmiah UNISBA, 2024)
Abstract. Subang University has used the online Academic Information System (SIAKAD) as a technology adoption. The problem is that not all faculties use SIAKAD optimally. Therefore, it is important to find out factors that influence user satisfaction to increase user satisfaction with SIAKAD services. This research aims to provide recommendations to increase user satisfaction with SIAKAD services and enhance the efficiency and effectiveness of administrative processes at Subang University. The Unified Theory of Acceptance and Use of Technology (UTAUT) 3 and Technology Acceptance Model (TAM) methods are utilized in this study. This method model of UTAUT 3 is chosen since it has more complete variables than UTAUT 1 and UTAUT 2. This research combines the three main variables from UTAUT 3 with the two main variables from TAM. The three main UTAUT 3 variables used are the usability variable, the ease-of-use variable, and the self-motivation variable. This study tests the model using the PLS-SEM technique and SmartPLS software. Test findings show that Behavioral Intention is influenced positively and significantly by Facilitating Conditions and Performance Expectancy. Meanwhile, Use Behavior is positively and significantly impacted by Behavioral Intention.